Poor Eating Habits and Selected Determinants of Food Choice Were Associated With Ultraprocessed Food Consumption in Brazilian Women During the COVID-19 Pandemic - Smaira, Fabiana Infante; Mazzolani, Bruna Caruso; Esteves, Gabriel Perri; André, Heloisa C. Santo; Amarante, Milla Cordeiro; Castanho, Daniela Fernandes; Campos, Karen Jennifer de; Benatti, Fabiana Braga; Pinto, Ana Jéssica; Roschel, Hamilton; Gualano, Bruno; Nicoletti, Carolina Ferreira (Frontiers in Nutrition, 2021)
Participants (n=629) were aged 34.0 years and mostly within normal weight according to BMI (60.4%). “Snacking” and “liking” associated with increased energy (β=164.27 and β=110.24) and carbohydrate intake (β=1.97 and β=1.80), and with reduced protein intake (β=-1.54 and β=-1.18). In contrast, “dieting” and “weight control” associated with reduced energy (β=-162.57 and β=-111.49) and carbohydrate intake (β=-2.78 and β=-2.07), and with increased protein intake (β=3.78 and β=1.65). “Dieting” (β=7.27), “need and hunger” (β=3.34) and “health” (β=4.94) associated with an increased consumption of unprocessed and minimally processed foods, whereas “replacing main meals with snacks” (β=-8.98), “snacking” (β=-6.92) and binge eating symptoms (β=-0.34) associated with reduced consumption of foods within this processing level. In contrast, “use of delivery services” (β=3.39), “replacing main meals with snacks” (β=5.49), “visual appeal” (β=2.17), “social norms” (β=2.19) and “affect regulation” (β=2.01) associated with increased ultraprocessed food consumption. Overall, associations were more frequent and pronounced when analyzing food consumption by processing level rather than by macronutrient intake. Conclusion: Some eating habits and food choice determinants (“snacking”, “replacing meals with snacks”, “use of delivery services”) observed during the COVID-19 pandemic were associated with an unhealthy diet (high energy and carbohydrate consumption, increased ultraprocessed food consumption and reduced unprocessed/minimally processed foods consumption) in Brazilian women.